2022
DOI: 10.3390/curroncol29030157
|View full text |Cite
|
Sign up to set email alerts
|

Living Donor Liver Transplantation for Intrahepatic Cholangiocarcinoma

Abstract: Intrahepatic cholangiocarcinoma is in most transplant regions a contraindication for liver transplantation, even ruling out an active waiting list registration. However, recent studies showed that well-selected patients after a neo-adjuvant treatment benefit from liver transplantation with good long-term outcomes. The role of living donor liver transplantation is unclear for this indication. The current study focuses on LDLT for intrahepatic cholangiocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Given this background, LDLT appears to be an excellent procedure from an organizational view, as surgical exploration and lymphadenectomy can be performed prior to donor surgery as demonstrated in our case. With 7 % of all liver transplantations, LDLT represents the minority of transplantations in the Eurotransplant area, but provides a useful addition to the organ pool especially in cases of missing options within the standard allocation system [22]. Nevertheless, iCCA appears to be a rare indication for LDLT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given this background, LDLT appears to be an excellent procedure from an organizational view, as surgical exploration and lymphadenectomy can be performed prior to donor surgery as demonstrated in our case. With 7 % of all liver transplantations, LDLT represents the minority of transplantations in the Eurotransplant area, but provides a useful addition to the organ pool especially in cases of missing options within the standard allocation system [22]. Nevertheless, iCCA appears to be a rare indication for LDLT.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, iCCA appears to be a rare indication for LDLT. In a recent report from 2022, Rauchfuß et al identified only 6 case reports of patients who underwent LDLT for iCCA [22].…”
Section: Discussionmentioning
confidence: 99%
“…Their study revealed a three-year survival rate of 63% ( 32 ). We resume the cases series in Table 1 , including our first reported case ( 33 37 ).…”
Section: Ldlt For Iccmentioning
confidence: 99%
“…ICC has been considered an absolute contraindication to liver transplantation in the past [19] , but recent studies have shown that liver transplantation can achieve acceptable survival outcomes in patients ICC patients with proper selection criteria such as very early stage, small tumor volume (≤ 2cm), and single tumor [20] . Additionally, neoadjuvant chemotherapy enables patients with locally advanced and unresectable ICC to bene t from liver transplantation with favorable long-term outcomes [21,22] .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, neoadjuvant chemotherapy enables patients with locally advanced and unresectable ICC to bene t from liver transplantation with favorable long-term outcomes [21,22] . However, liver transplantation is greatly limited by the severe shortage of donors and the associated postoperative immunosuppression, which is an ordeal for patients and is capable of promoting tumor recurrence or metastasis [19] . Data on survival after neoadjuvant chemotherapy and subsequent liver transplantation are currently limited, necessitating the establishment of large sample studies to further evaluate the signi cance of this treatment strategy [23] .…”
Section: Introductionmentioning
confidence: 99%